Process dynamics and control - Seborg, Dale E.; Edgar, Thomas F.; Mellichamp, Duncan A. (John Wiley & Sons, 2004)
Reflects changes and advances in process control theory and technology. This title includes topics on mathematical modeling of chemical processes, developing dynamic models from process data, control system design, process safety and process control, enhanced single loop control, digital control, and multiloop and multivariable control.